Papel do extrato etanólico bruto de Trichoderma stromaticum na infecção de camundongos C57BL/6 por Plasmodium berghei ANKA - Sifontes, Yusmaris Josefina Cariaco (2017)
Malaria is a severe health problem. The first-line treatment against the disease are the artemisinin-based combination therapies. However, increased resistance to these drugs has been reported. The aim of this study was to evaluate the role of crude etanolic extracts of Trichoderma stromaticum (Ext-Ts) in C57BL/6 mice infected with Plasmodium berghei ANKA, a well-known model of experimental cerebral malaria. Clinical, histological, immunological and biochemical features of the infection were monitored. It was found that Ext-Ts treatment was able to prevent neurological alterations associated with experimental cerebral malaria, decreased parasitemia levels and significantly improved survival of infected animals. Furthermore, it was observed that in Ext-Ts-treated mice a reduction of total serum cholesterol, triglycerides and TGP, lower hemozoin deposition into the liver, attenuation of pulmonary edema intensity, integrity of the blood-brain barrier as well as fewer cytoadherence and histopathological findings in assessed tissues in comparison with untreated infected mice. This protection was associated with decreased IFN-γ and ICAM-1 mRNA expression in brain of treated animals compared with untreated animals. These results suggest that Ext-Ts is a potential source of antimalarial and immunomodulatory compounds that could improve the current treatment in the context of resistance to artemisinin derivatives.